2022
DOI: 10.1111/and.14510
|View full text |Cite
|
Sign up to set email alerts
|

Do sclero‐embolization procedures have advantages over surgical ligature in treating varicocele in children, adolescents and adults? Results from a systematic review and meta‐analysis

Abstract: We aimed to systematically review complications, and recurrence rate of varicocele treatment by comparing the surgical ligature versus sclero-embolization techniques in children, adolescents and adults. The secondary outcomes were the evaluation of semen parameters and spontaneous pregnancy rate in adults. The review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses framework. Continuous variables were pooled using the inverse variance of the mean difference (MD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Of these, six studies assessed pregnancy after embolisation and the meta‐analysis showed successful pregnancy in 91 of 222 patients at a rate of 40.99%. The rate was similar between surgical repair and embolisation (40.99% vs. 41.58%, OR 1.03, P = 0.97) 2 …”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Of these, six studies assessed pregnancy after embolisation and the meta‐analysis showed successful pregnancy in 91 of 222 patients at a rate of 40.99%. The rate was similar between surgical repair and embolisation (40.99% vs. 41.58%, OR 1.03, P = 0.97) 2 …”
Section: Introductionmentioning
confidence: 77%
“…To calculate cost per pregnancy, costs were adjusted according to existing published data on the rate of pregnancy after varicocoele embolisation. The authors chose to use the highest quality data at the time of publishing as thus used results of the recent meta-analysis published by Fabiani et al 2 In this study, the authors showed pregnancy after embolisation in 91 of 222 patients, a rate of 0.4099. As such, we calculated the cost per pregnancy as the median total cost divided by the published pregnancy rate.…”
Section: Pregnancy Ratementioning
confidence: 99%
See 3 more Smart Citations